Smart Dynamic Concrete-Rapid Economical Sustainable Construction: Enhancing Self-Compacting Concrete with Smart Dynamic Concrete (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The innovative Self Compacting Concrete (SCC) was first introduced in Japan in early 1980’s. The use of SCC was spreaded all over the world for precast and ready mix concrete industry. Although, there is limited use of SCC because of its initial higher cost of production. To prevent bleeding and segregation, SCC mixes need high amount of cementatious material. Then only it can deliver self-compacting properties. To overcome this high fines content a new concept was introduced in Asian market, named as “Smart Dynamic Concrete”. With the SDC it is possible to reduce high fines content without losing self-compacting property. The production of SDC made possible by using an innovative new family member of viscosity modifying agent admixture (VMA) in the combination with super-plasticizer.